2022
DOI: 10.37077/25200860.2022.35.2.24
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Foliar Application of Nano-selenium on the Anatomical Characteristics of Date Palm Phoenix dactylifera L. Barhi Cultivar under Salt Stress

Abstract: This study investigated the effect of salinity on the anatomical features of date palm (Phoenix dactylifera L.) and the potential roles of nano selenium (Se NPs) in alleviating the adverse effects of salinity. Two concentrations (80 and 160 mg.L-1) of SeNPs were applied as a foliar spray on date palms irrigated with different concentrations of saline water (2.5 [control], 5, 10 and 20 ds.m-1). Results showed that 5 ds.m-1 salinity had no significant effect on the anatomical structure of date palm, whether appl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
1
0
Order By: Relevance
“…These findings are consistent with those reported by the authors of [ 53 ], who found that Zn and Se are crucial for promoting the chlorophyll scale and relieving all harmful outcomes caused by abiotic stress. In addition, Se-NPs improved the vascular bundle dimensions and thickness of mesophyll, xylem, and phloem, as well as the thickness of the lower and upper epidermis of Date Palm plants under salinity stress [ 54 ]. However, all anatomical characteristics decreased in the control plants.…”
Section: Discussionmentioning
confidence: 99%
“…These findings are consistent with those reported by the authors of [ 53 ], who found that Zn and Se are crucial for promoting the chlorophyll scale and relieving all harmful outcomes caused by abiotic stress. In addition, Se-NPs improved the vascular bundle dimensions and thickness of mesophyll, xylem, and phloem, as well as the thickness of the lower and upper epidermis of Date Palm plants under salinity stress [ 54 ]. However, all anatomical characteristics decreased in the control plants.…”
Section: Discussionmentioning
confidence: 99%
“…The date palm is a hardy fruit crop species that grows well in arid and semiarid climates. Its capacity to store particular metabolites within its cells, which provide tolerance to a range of environmental challenges, such as heat, salt, drought and damaging radiations, is the source of its adaptability [11][12][13]. Date palms produce amino acids, including L-cysteine, ketoleucine, N-acetyl-L-aspartate, L-tyrosine and homocysteine, through their internal metabolism in response to UV-B damage.…”
Section: Introductionmentioning
confidence: 99%